Shape Preservation of the Stationary 4-Point Quaternary Subdivision Schemes - Pervez, Khurram (Communications in Mathematics and Applications, 2018)
In this paper, the shape preserving properties of the stationary 4-point quaternary approximating and interpolating subdivision schemes of Ko [9] are fully investigated. We will analyzed what conditions should be introduced on the initial control points so that the limit curve achieved by the subdivision schemes presented in [9] are both monotonicity and convexity preserving. Conclusively the whole discussion is followed by examples.